Simply irresistible - Gellar, Sarah Gilliard 1977-; Flanery, Sean Patrick 1965-; Fiedler, John 1925-2005; Amiel, Jon 1948-; Caracciolo, Joe; Roberts, Judith 1934-; Tarlov, Mark (Beverly Hills, California Twentieth Century Fox Home Entertainment, 1999)
Beautiful restaurant owner Amanda Shelton is falling head over heels for handsome, hard-driving executive Tom Bartlett. Unfortunately, Tom is too busy to recognize that she's truly the girl of his dreams...until Amanda put him under her tantalizing spell!
Music by Gil Goldstein ; Co-producer, Brian Maas ; Director of photography, Robert Stevens ; Executive producers, Arnon Milchan, Elisabeth Robinson.
Sarah Michelle Gellar, Sean Patrick Flanery, Patricia Clarkson, Dylan Baker, Christopher Durang, Larry Gilliard, Jr., Betty Buckley.
VHS format.
In English.
Keywords: Man-woman relationships -- Drama; Romance films